THE IMPACT OF VIDEO ANIMATION ON THE LISTENING ABILITY OF 9TH GRADE STUDENTS OF MTS MA’ARIF NU KOTA MALANG - Sinta Kristina Fauzi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The aim of this article is to knowing the impact of video animation on the listening ability of 9th grade students of MTS Ma’arif NU Kota Malang. In this research, the researcher used pre-experimental design and utilized SPSS to calculated the result of data. The result of this study known that the value of sig. (2-tailed) 0.001 <0.05. It means, there is difference score between the pretest and posttest, which means that there is an impact of using video animation on students listening ability. This implies that the data is accepted and there is a significant difference between the result of learning Engish listening by using video animation on the pretest and posttest.Keywords: Listening, video animation, listening ability